A REVIEW OF ARTICLES ON INFRASTRUCTURE CONTRACTORS FINANCING IN THE ISLAMIC BANKING - Buana, Mohamad Torik Langlang; Mohd Dali, Nuradli Ridzwan Shah (LPPM STIE Muhammadiah Bandung, 2023)
Construction has become a prominent research topic by many authors from different areas but not in the field of Islamic finance. In financing the infrastructure contractors, the banking industry might be faced with evaluating the overall infrastructure project or the capability of an infrastructure project themselves. Therefore, financing for the construction project or contractor is in a grey area. This paper aims to analyse the topic of study in academic articles authored by scholars about financing the infrastructure construction sector by Islamic banks, in particular infrastructure contractors. Many papers related to financing by Islamic banks discuss fiqh, law, and economic aspects. This is a systematic literature review and was conducted by screening three databases namely Scopus, Ebscohost, and ProQuest from 2001 to 2021. The search was initiated by using three combinations of keywords: Islamic banks, contractors, and infrastructure. The result found that there was a gap in the theoretical and practical knowledge of financing the contractors by Islamic banks. Many papers discuss construction financing using Islamic finance and banking for the full-phase construction segment rather than discussing the contractors.